The Effect of Social Support on Stress Levels of Health Workers During The COVID-19 Pandemic: A Literature Review - Riris Diana Rachmayanti; Kamila Fihir Bawazier; Takako Yasutome; Rachmah Indawati; Aninditya Ardhana Riswari; Ismayani Ismayani; Andrei Ramani; Anysiah Elly Yulianti; Jayanti Dian Eka Sari (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: The COVID-19 pandemic has caused various changes in the social dynamics of life. Almost all age groups in various countries are forced to adopt new habits that have the potential to interfere with mental health. Providing social support can be useful for reducing the stress level of health workers. Proper social support can overcome stress problems. The purpose of this study was to analyze the effect of social support on the stress level of health workers during the COVID-19 pandemic.Method: This is a literature review using population, intervention, comparison, results, research design, and keywords used according to the research topic. Keyword use Mesh term strategy with the term "social support" stress" "worker" "pandemic" and "COVID". Database sources are ScienceDirect, PubMed, Google Scholar, and SAGE. Searching strategy uses Prisma guidelines. The total article was 2,226 and the eligible article was 24 articles. The collected data were analyzed through a thematic review. The data analysis technique in this study was descriptive analysis.Results: The results of the study show that most health workers experience moderate levels of stress during the pandemic. The most influential sources of social support come from colleagues and partners. The form of social support that is often received and influences stress levels is emotional support. There is an effective effect of social support on the stress level of health workers during the pandemic. Therefore, it can be concluded that adaptation during COVID-19 has caused various changes in conditions and pressure for health workers